Backstepping attitude control for hypersonic gliding vehicle based on a robust dynamic inversion approach. (September 2014) - Liu, Xiaodong; Zhang, Yu; Wang, Sen; Huang, Wanwei
A novel nonlinear attitude control method is proposed for hypersonic gliding vehicle by using a robust dynamic inversion control approach. The special objective of this control scheme is to deal with the parameter perturbations, high uncertainties and strong couplings during the flight of hypersonic gliding vehicle. According to the attitude motion equations of unpowered hypersonic gliding vehicle, a nonlinear model facing to attitude controller design is established. With regard to a class of nonlinear system, a robust dynamic inversion control is proposed and then applied to the hypersonic gliding vehicle attitude control by using backstepping approach. The stability conditions of hypersonic gliding vehicle attitude control system are obtained by means of Lyapunov function method. Simulation results show that the chosen hypersonic gliding vehicle plant using the proposed control scheme possesses better tracking performances, with respect to rapidity, accuracy and stability, compared to another backstepping control scheme based on traditional dynamic inversion control. Furthermore, it also has stronger robustness against system uncertainties.